2015
DOI: 10.1017/s0954579415001091
|View full text |Cite
|
Sign up to set email alerts
|

Familial influences on the full range of variability in attention and activity levels during adolescence: A longitudinal twin study

Abstract: To investigate familial influences on the full range of variability in attention and activity across adolescence, we collected maternal ratings of 339 twin pairs at ages 12, 14 and 16, and estimated the transmitted and new familial influences on attention and activity as measured by the Strengths and Weaknesses of ADHD Symptoms and Normal Behavior Scale (SWAN). Familial influences were substantial for both traits across adolescence: genetic influences accounted for 54–73% (attention) and 31–73% (activity) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…The SWAN generates heritable trait scores that are widely and virtually normally distributed in the general population (Couvy-Duchesne et al, 2016;Crosbie et al, 2013;Greven et al, 2016;Hay et al, 2007;Peng et al, 2016;Polderman et al, 2007;Smit & Anokhin, 2017). To add support to the validity of the SWAN, we showed that high SWAN scores converge with a clinical diagnosis of ADHD consistent with the quantitative trait notion of psychopathology and SWAN (parent-and self-report) scores show convergent and divergent validity against other measures of ADHD, anxiety and OCD traits.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The SWAN generates heritable trait scores that are widely and virtually normally distributed in the general population (Couvy-Duchesne et al, 2016;Crosbie et al, 2013;Greven et al, 2016;Hay et al, 2007;Peng et al, 2016;Polderman et al, 2007;Smit & Anokhin, 2017). To add support to the validity of the SWAN, we showed that high SWAN scores converge with a clinical diagnosis of ADHD consistent with the quantitative trait notion of psychopathology and SWAN (parent-and self-report) scores show convergent and divergent validity against other measures of ADHD, anxiety and OCD traits.…”
Section: Discussionmentioning
confidence: 65%
“…It is reliable, generates normally distributed scores in the general population, has high internal consistency, high test-retest reliability, converges reasonably with ADHD symptom measures and diverges from measures of emotionality (Arnett et al, 2013;Crosbie et al, 2013;Lai et al, 2013;Lakes, Swanson, & Riggs, 2012;Stroud et al, 2009;Swanson et al, 2012). Twin and sibling studies established the heritability (h 2 ) of the parent-and self-report SWAN (h 2 =0.24-0.94; Couvy-Duchesne et al, 2016;Crosbie et al, 2013;Greven et al, 2016;Hay, Bennett, Levy, Sergeant, & Swanson, 2007;Peng et al, 2016;Polderman et al, 2007;Smit & Anokhin, 2017). A GWAS using the SWAN identified suggestive genome-wide significant hits (n=1851; Ebejer et al, 2013).…”
mentioning
confidence: 99%
“…The current study adds to the previous literature to support the SWAN as a valid tool for use in quantitative genetic research. The SWAN generates heritable trait scores that are widely and virtually normally distributed in the general population (Couvy‐Duchesne et al., ; Crosbie et al., ; Greven et al., ; Hay et al., ; Peng et al., ; Polderman et al., ; Smit & Anokhin, ). In this study, we showed that high SWAN scores converged with a diagnosis of ADHD in both Spit for Science and clinical samples consistent with the notion that ADHD is the extreme of a quantitative trait.…”
Section: Discussionmentioning
confidence: 99%
“…It is reliable, generates normally distributed scores in the general population, has high internal consistency, high test‐retest reliability, converges reasonably with ADHD symptom measures and diverges from measures of emotionality (Arnett et al., ; Crosbie et al., ; Lai et al., ; Lakes, Swanson, & Riggs, ; Stroud et al., ; Swanson et al., ). The parent‐ and self‐report SWAN are heritable ( h 2 = 0.24–0.94; Couvy‐Duchesne et al., ; Crosbie et al., ; Greven et al., ; Hay, Bennett, Levy, Sergeant, & Swanson, ; Peng et al., ; Polderman et al., ; Smit & Anokhin, ). An underpowered GWAS ( n = 1,851) using the SWAN identified suggestive genome‐wide significant hits (Ebejer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, it was biologically valuable to hypothesize an association between the Val158Met polymorphisms of COMT gene and clinical phenotypes in ADHD children[7][8][9]. According to this hypothesis, G (valine) variant of COMT gene was associated with the faster depletion of catecholaminergic neurotransmitters from synapses in the prefrontal cortex[10][11][12][13].Recent studies have suggested that the Val158Met polymorphisms of COMT gene might be involved in the pathogenesis of ADHD children. Eisenberg et al found that G/A variations of COMT gene had a significant relation with ADHD children.…”
mentioning
confidence: 88%